Analisis Faktor Prioritas Daerah Resapan Air di Kota Denpasar Provinsi Bali - NI PUTU UTARI HANDAYANI; NI MADE TRIGUNASIH; PUTU PERDANA KUSUMA WIGUNA; I WAYAN SEDANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Analysis Priority Factor of Water Catchment Area in Denpasar City Bali Province Denpasar City as the capital city and one of the tourism centers in Bali Province is experiencing an increasing need for residential land use, because Denpasar City has a fairly large population. This causes a reduction in the water catchment area, so that most of the water becomes runoff. Determination of water catchment areas in all areas using the same factors, namely, soil type, rainfall, slope, and land use. However, each factor will be influenced by environmental conditions which cause each factor to have a different priority value. Therefore, it is necessary to study the priority factors of water catchment areas in Denpasar City. This research was conducted from September to December 2021. The purpose of this study was to determine the determinants of water catchment areas in Denpasar City and the priority value of each factor. This study utilizes spatial technology, namely Geographic Information Systems (GIS) which uses the Spatial Multi Criteria Evaluation (SMCE) to determine the weight and priority value of the determinants of water catchment areas. This research produces an output in the form of a map of each of the determinants of water catchment areas. The results showed that the soil type factor became the first priority, the rainfall factor became the second priority, the land use factor became the third priority, and the slope factor became the last priority.